K-Rod: An Innovative Method of Personalized Rib Splinting for Expeditious Management of Flail Chest in Acute Care Settings - Chia-Jung Lin; Yung-Sung Yeh; Yen-Ko Lin; Chao-Wen Chen (Medicina, 2022)
Flail chest is a severe type of multiple rib fracture that can cause ventilation problems and respiratory complications. Historically, flail chest has been mainly managed through pain control and ventilatory support as needed. Operative fixation has recently become popular for the condition, and some studies have revealed its potentially positive effects on the outcomes of patients with flail chest. However, for those for whom surgery is unsuitable, few treatment options, other than simply providing analgesia, are available. Herein, we introduce our innovative method of applying personalized rib splinting for quick management of flail chest, which is easy, tailor-made, and has significant effects on pain reduction.